What human blood-brain barrier models can tell us about BBB function and drug discovery? - Ferreira, Lino (2019)
Introduction: Human in vitro blood-brain barrier (BBB) models could be important tools for studying BBB development, maintenance and regulation. However, our capacity to obtain information from these models is still limited in part because only in recent years have (i) these models been derived from non-brain cell sources (e.g. stem cells), (ii) microfluidic systems been developed to recapitulate aspects of BBB physiology and (iii) new insights into the molecular and cellular mechanisms of BBB diseases (e.g. Huntington´s, Allan-Herndon-Dudley Syndrome) been described. Area covered: This article reviews the technological advances in the derivation of human cells from the neurovascular unit using stem cells and the creation of personalized BBB models generated from patients with neurodegenerative diseases. It also reviews the scientific advances generated from in vitro BBB models. Expert opinion: The recent technological advances in the derivation of human cells from the neurovascular unit from stem cells as well as in the generation of BBB-on-a-chip that recapitulate in vitro part of the BBB physiology are significant to generate more robust BBB models; however, a considerable effort is still needed to validate the potential of these models to recapitulate the in vivo cellular and molecular mechanisms, in particular regarding BBB function in health and disease.